(untitled) (Third Sector Social Economic Review, 2017)
Recently, the importance of trust which is the base of interpersonal communication, is better understood by the companies and the number of internal trust studies have accelarated. The purpose of this study is to investigate the relationship between trust in supervisor and trust in organization, and internal communications channels and perceived sources of power. The study results revealed that both internal communication and perceived sources of power are related to trust in supervisor and trust in the company. The analyses shows that formal communication contributes to the level of trust in both supervisor and company the most. The increase in referent and expert power of the supervispr also increases the level of trust in both supervisor and company. However, when employees sense that their supervisors are using coersive power, their trust in both supervisor and organization decrease. The findings are discussed in detail.